Clinical implications and current perspectives of statin-induced rhabdomyolysis syndrome - case presentation - Ciobanu Elena Cosmina; Ungurenasu Andreea Simona; Haba Mihai Ștefan Cristian; Petris Antoniu Octavian; Mitu Ovidiu (Sciendo, 2022)
Though rare, statins can produce serious adverse effects with clinical implications that urge prompt intervention. However, in high-risk patients that require intense hypolipemiant treatment, such situations can be challenging and require complimentary therapies. We report the case of a 82-year-old hypertensive female patient admitted for diffuse myalgia, mainly in the lower limbs, fatigue and shortness of breath. The patient is known with a recent myocardial infarction (MI) treated by primary stent implantation. The electrocardiogram and transthoracic echocardiography confirmed the recent MI, with non-dilated left ventricle mildly reduced ejection fraction. Initial laboratory studies revealed elevated NT-proBNP, moderate renal impairment and increased serum levels of creatine kinase (CK), CK-MB fraction and transaminases. After stopping statin and receiving supportive treatment, the patient's paraclinical test results and symptoms improved: CK levels and transaminase dropped significantly and both myalgia and general fatigue resolved mostly within 4 days. PCSK9 inhibitor has been introduced with favourable results at follow-ups. Even though statins are effective and safe, they may still generate potential dangerous adverse effects in rare cases. Statin dose adjustment or replacement and adding other lipid lowering therapies represent current therapeutical options, especially in high-risk populations.